Strigolactones Interact With Nitric Oxide in Regulating Root System Architecture of Arabidopsis thaliana - Oláh, Dóra; Feigl, Gábor; Molnár, Árpád; Ördög, Attila; Kolbert, Zsuzsanna (Frontiers in Plant Science, 2020)
Both nitric oxide (NO) and strigolactone (SL) are growth regulating signal components in plants; however, regarding their possible interplay our knowledge is limited. Therefore, this study aims to provide new evidence for the signal interplay between NO and SL in the formation of root system architecture using complementary pharmacological and molecular biological approaches in the model Arabidopsis thaliana grown under stress-free conditions. Deficiency of SL synthesis or signalling (max1-1 and max2-1) resulted in elevated NO and S-nitrosothiol (SNO) levels due to decreased S-nitrosoglutathione (GSNO) reductase (GSNOR) protein abundance and activity indicating that there is a signal interaction between SLs and GSNOR-regulated levels of NO/SNO. This was further supported by the down-regulation of SL biosynthetic genes (CCD7, CCD8 and MAX1) in GSNOR-deficient gsnor1-3. Based on the more pronounced sensitivity of gsnor1-3 to exogenous SL (rac-GR24, 2 µM), we suspected that functional GSNOR is needed to control NO/SNO levels during SL-induced primary root (PR) elongation. Additionally, SLs may be involved in GSNO-regulated PR shortening as suggested by the relative insensitivity of max1-1 and max2-1 mutants to exogenous GSNO (250 µM). Collectively, our results indicate a connection between SL and GSNOR-regulated NO/SNO signals in roots of A. thaliana grown in stress-free environment. As this work used max2-1 mutant and rac-GR24 exerting unspecific effects to both SL and karrikin signalling, it cannot be ruled out that karrikins are partly responsible for the observed effects and this issue needs further clarification in the future.